Evaluation of the development process of selcuk university faculty of veterinary medicine between 1992-2022 (30 years) - Emine Merve Danis; Esra Celik; Askin Yasar; Gokhan Aslim (Eurasian Journal of Veterinary Sciences)
Aim: This study, it was aimed to reveal the development process of Selcuk University Faculty of Veterinary Medicine between 1992-2022. Materials and Methods: The material of the study consisted of information and documents obtained by the Rector?s Office of SU, the Deans Office of the SUFVM and the SU Veterinary Training and Practice Hospital, an archive of the SU Health Sciences Institute, and the ?Scientific Research and Publication List Form.? In addition, the Official Gazette, journals, books, and internet resources on the subject and Yaşar?s (1995) research were used. The data obtained were evaluated by the content analysis method, indicated as superscript in the text, shown in the endnote section, and presented in tables in the relevant section. Results: It was determined that as of the 2021-2022 academic year, a total of 136 academic staff members were serving in 20 departments at the faculty 3.806 undergraduate and 693 postgraduate graduates (460 Ph.D., 233 masters) (1987-2022) graduated from the faculty in the last 30 years; veterinary medicine services were provided to 24.335 animals in the faculty animal hospital in 2022. Conclusion: The current study aims to complete the 40-year development process by revealing the 30-year development of SUFVM. Following the development of the faculty in the future will contribute to increasing its preferability in the national and international arena by moving the faculty further in every field.